Estimating risk of natural gas portfolios by using GARCH-EVT-Copula model - Jiechen Tang (2018)
© 2014 Jiechen Tang et al. This paper concentrates on estimating the risk of Title Transfer Facility (TTF) Hub natural gas portfolios by using the GARCHEVT-copula model.We first use the univariate ARMA-GARCH model tomodel each natural gas return series. Second, the extreme value distribution (EVT) is fitted to the tails of the residuals to model marginal residual distributions.Third, multivariate Gaussian copula and Student t-copula are employed to describe the natural gas portfolio risk dependence structure. Finally, we simulate N portfolios and estimate value at risk (VaR) and conditional value at risk (CVaR). Our empirical results show that, for an equally weighted portfolio of five natural gases, the VaR and CVaR values obtained fromthe Student t-copula are larger than those obtained fromthe Gaussian copula.Moreover, when minimizing the portfolio risk, the optimal natural gas portfolio weights are found to be similar across the multivariate Gaussian copula and Student t-copula and different confidence levels.